Psychological Predictors of Outcomes with Lumbar Spinal Fusion: A Systematic Literature Review. (13th August 2015) - Wilhelm, Mark; Reiman, Michael; Goode, Adam; Richardson, William; Brown, Christopher; Vaughn, Daniel; Cook, Chad
Abstract: Purpose: To review the predictive/risk psychological factors at baseline that are associated with a favourable (or non‐favourable) outcome following lumbar spinal fusion (LSF). Methods: A computer‐assisted literature search of PubMed, CINAHL complete and EMBASE for studies published between January 1, 1990 and October 1, 2014 with controlled vocabulary and key words related to LSF, degenerative lumbar spine diagnoses and appropriate terms for predictive variables. Each study was required to be a retrospective or prospective design that involved LSF (all forms). Quality assessment was conducted with the Quality In Prognosis Studies tool. A study protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO# CRD42014008728). Results: The majority of the eight accepted studies were observational, prospective cohorts (n = 6). High levels of baseline depression and lower SF‐36 Mental Component Scores (MCS) lower quality of life were associated with non‐favourable outcomes. Two studies were rated as high quality, five were moderate and one study had low quality. Conclusions: At present, there are a number of psychological variables that are associated with a poorer outcome with LSF. Higher levels of depression and lower scores on the SF‐36 MCS are the most commonly implicated. However, based on the results of the studies using single arm designs there is not enough evidence to determine which psychological variables are influential in predicting outcomes for LSF. Copyright © 2015 John Wiley & Sons, Ltd.